2018
DOI: 10.7554/elife.33569
|View full text |Cite
|
Sign up to set email alerts
|

Codon usage biases co-evolve with transcription termination machinery to suppress premature cleavage and polyadenylation

Abstract: Codon usage biases are found in all genomes and influence protein expression levels. The codon usage effect on protein expression was thought to be mainly due to its impact on translation. Here, we show that transcription termination is an important driving force for codon usage bias in eukaryotes. Using Neurospora crassa as a model organism, we demonstrated that introduction of rare codons results in premature transcription termination (PTT) within open reading frames and abolishment of full-length mRNA. PTT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 99 publications
(192 reference statements)
1
52
0
1
Order By: Relevance
“…Interestingly, in a separate study in Neurospora, gene expression modulated by codon usage was shown to be due to the effects of transcription rather than translation [67]. In a follow-up study, the group also demonstrated C/G bias is able to promote gene expression by suppressing premature transcription termination [68]. In addition, several other studies have demonstrated that in mammalian cells, GC-rich genes are transcribed with increased efficiency, resulting in higher levels of transcripts independent of mRNA degradation [69,70].…”
Section: Investigating the System Of Codon Bias In Humansmentioning
confidence: 96%
“…Interestingly, in a separate study in Neurospora, gene expression modulated by codon usage was shown to be due to the effects of transcription rather than translation [67]. In a follow-up study, the group also demonstrated C/G bias is able to promote gene expression by suppressing premature transcription termination [68]. In addition, several other studies have demonstrated that in mammalian cells, GC-rich genes are transcribed with increased efficiency, resulting in higher levels of transcripts independent of mRNA degradation [69,70].…”
Section: Investigating the System Of Codon Bias In Humansmentioning
confidence: 96%
“…To test whether S. cerevisiae coding sequences might be depleted of splicing signals, we compared their frequency in the ORF set of the extant S. cerevisiae genome with that in 10,000 synthetic ORF sets derived by randomizing the order of codons for each ORF. This approach maintains ORF length, integrity, GC content, and codon usage in the permuted ORF sets while generating partially randomized nucleotide sequences that can be used as a background sequence set for comparison, and has been used to evaluate co-evolution of RNA processing signals within coding sequence [58].…”
Section: Coding Regions Are Depleted Of Sequences Required For Splicingmentioning
confidence: 99%
“…Although the effect of codon usage on overall transcription has been widely studied and debated [60][61][62] , their surprisingly strong effects on transcription, also supported by our results (Fig 2B), have only recently started coming to light. The hypothesized mechanisms through which codons affect transcription are: (i) effects on nucleosome positioning 37 , (ii) premature termination of transcription, usually by mimicking poly-A signals 63 , or (iii) mRNA toxicity 64 . Generally, the differences in codon usage between bacterial species can be explained from the dinucleotide content in their non-coding regions 65 and it is widely assumed that most inter-species variation in codon usage is attributed to mutational mechanisms 60,66 .…”
Section: Discussionmentioning
confidence: 99%